San Martín, el “territorio libre” de las intendencias de Tarma y de Trujillo y la Independencia del Perú - O’Phelan Godoy, Scarlett (2023)
On February 12, 1821, San Martín gave a provisional regulation on the territory that had been liberated by the patriot forces and that, therefore, was no longer governed by the Spanish government. The space corresponded to the province and intendancies that he had liberated in 1820, since his arrival in Peru. It included the province of Chancay, where he had established his headquarters in Huaura, the intendancy of Tarma, where the mine of Pasco was located, and the intendancy of Trujillo, of great extension and that included the provinces of northern Peru, crossing the coast, highlands and jungle. This article analyzes the process of incorporation of this territory to the domain of the Patriotic Army.